Heat recovery steam generator technology - Eriksen, Vernon L. (Duxford, United Kingdom Woodhead Publishing, 2017)
Heat Recovery Steam Generator Technology is the first fully comprehensive resource to provide readers with the fundamental information needed to understand HRSGs. The book's highly experienced editor has selected a number of key technical personnel to contribute to the book, also including burner and emission control device suppliers and qualified practicing engineers. In the introduction, various types of HRSGs are identified and discussed, along with their market share. The fundamental principles of the technology are covered, along with the various components and design specifics that should be considered. Its simple organization makes finding answers quick and easy. The text is fully supported by examples and case studies, and is illustrated by photographs of components and completed power plants to further increase knowledge and understanding of HRSG technology.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Waste heat boilers; Electronic books